The early stage of COVID-19 pandemic: Gastrointestinal manifestations and liver injury in COVID-19 patients in Wuhan, China - Chen, Dafan; Ning, Min; Feng, Yun; Liu, Jun (Frontiers in Medicine, 2022)
Objectives: There are few and inconsistent data focusing on gastrointestinal (GI) manifestations and liver injury in the early stage of COVID-19 pandemic in China. In this study, we research the prevalence and role of GI symptoms and liver injury in COVID-19 patients in Wuhan during the course of disease first outbreak. Methods: A cross-sectional observational study was conducted in a non-ICU unit in Wuhan, China. COVID-19 patients were consecutively admitted from 23 February 2020 to 5 April 2020. Demographic and clinical data were retrieved and analyzed throughout the disease course. Results: A total of 93 patients were enrolled, including 45.2% moderate, 54.8% severe and 2.2% critical type patients. 69.9% patients had at least one GI symptom; if excluding hyporexia/anorexia, 49.5% patients showed at least one GI symptom. The incidence rate of hyporexia/anorexia, diarrhea, nausea/vomiting, abdominal discomfort/pain, and elevated liver enzymes were 67.7%, 29.0%, 28.0%, 21.5% and 23.7%, respectively. Patients with GI symptoms or elevated liver enzymes have higher risk of severe type disease than patients without GI symptoms or elevated liver enzymes (67.7% vs 25.0%, p＜0.001; 77.3% vs 47.9%, p=0.016, respectively), and experienced longer disease duration. At multivariate analysis, hyporexia/anorexia was confirmed as an independent predictive factor of severe type disease (odds ratio: 5.912; 95% confidence interval: 2.247–15.559; p＜0.001). Conclusion: In the early stage of COVID-19 pandemic, GI symptoms and elevated liver enzymes are common throughout the disease course, and associated with severer disease and longer disease duration.